Efficient metabolic pathway modification in various strains of lactic acid bacteria using CRISPR/Cas9 system for elevated synthesis of antimicrobial compounds - Haryani, Yuli; Abdul Halid, Nadrah; Goh, Sur Guat; Mahmud Ab Rashid, Nor-Khaizura; Md Hatta, Muhammad Asyraf; Sabri, Suriana; Radu, Son; Hasan, Hanan (Elsevier, 2024)
Lactic acid bacteria (LAB) are known to exhibit various beneficial roles in fermentation, serving as probiotics, and producing a plethora of valuable compounds including antimicrobial activity such as bacteriocin-like inhibitory substance (BLIS) that can be used as biopreservative to improve food safety and quality. However, the yield of BLIS is often limited, which poses a challenge to be commercially competitive with the current preservation practice. Therefore, the present work aimed to establish an optimised two-plasmid CRISPR/Cas9 system to redirect the carbon flux away from lactate towards compounds with antimicrobial activity by disrupting lactate dehydrogenase gene (ldh) on various strains of LAB. The lactic acid-deficient (ldhΔ) strains caused a metabolic shift resulting in increased inhibitory activity against selected foodborne pathogens up to 78 % than the wild-type (WT) strain. The most significant effect was depicted by Enterococcus faecalis-ldh∆ which displayed prominent bactericidal effects against all foodborne pathogens as compared to the WT that showed no antimicrobial activity. The present work provided a framework model for economically important LAB and other beneficial bacteria to synthesise and increase the yield of valuable food and industrial compounds. The present work reported for the first time that the metabolism of selected LAB can be manipulated by modifying ldh to attain metabolites with higher antimicrobial activity.